Investigating the vascular structure of the conjunctiva in patients using spherical mini-scleral contact lenses utilizing OCT-A imaging - Fateme Alipour; Parisa Abdi; Hassan Asadigandomani; Mehdi Khodaparast; Zahra Montazeriani; Marzieh Sajedi (Scientific Reports)
Abstract This study aimed to compare the outcomes of Optical Coherence Tomography-Angiography (OCT-A) with the clinical assessments conducted by an experienced ophthalmologist, as well as to analyze the alterations in the conjunctiva of individuals utilizing spherical scleral contact lenses. OCT-A imaging was conducted on 13 patients (mean age: 34.1 years, 10 males) in a prospective study at two time points: at least 8 h post-lens removal and 1-hour post-lens application. The scleral region in the quadrants (superior, inferior, temporal, and nasal) was designated as the region of interest (ROI), located 3 mm from the limbus. This ROI was further divided into two bands: Band 1 (1.5 mm width under the lens) and Band 2 (1.5 mm width outside the lens). The vascular density ratios in the inferior quadrant were significantly reduced after the lens fitting: ROI (0.362 ± 0.074 post-lens vs. 0.452 ± 0.099 pre-lens, adjusted P-value = 0.027) and Band 1 (0.353 ± 0.075 post-lens vs. 0.462 ± 0.095 pre-lens, adjusted P-value = 0.008). In the superior (P-value = 0.026), inferior (P-value < 0.001), and temporal (P-value < 0.001) quadrants, the degree of conjunctival impingement, as scored by an experienced ophthalmologist using slit photographs, was significantly correlated with OCT-A findings. In conclusion, OCT-A identifies microvascular changes undetectable by slit-lamp examination, providing quantitative insights into vascular alterations from scleral lens use and complementing clinical evaluations.